Reformasi, Religious Diversity, and Islamic Radicalism after Suharto - Noorhaidi Hasan (Journal of Indonesian Social Sciences and Humanities, 2008)
This paper examines the rising tide of ethno-religious conflicts and Islamic radicalism in the political arena of post-Suharto Indonesia. In the climate of Reformasi that heralded freedom of expression, ethnic and religious violence flared up in various regions of Indonesia, threatening a society apparently imbued with a culture of tolerance based on harmonious inter-ethnic and inter-faith relations. In a flurry of conflicts, a number of militant Muslim groups arose and engulfed the political arena of post-Suharto Indonesia by calling for jihad and other violent actions. The rise of the groups gave a remarkable boost to the explosion of militant religious discourses and activism that threaten Indonesias reputation for practising a tolerant and inclusive form of Islam and threaten, too, the integrity of the Indonesian nation-state as well. Against the backdrop of the stateIslam relationship in the New Order, this paper looks at how this phenomenon is embedded in the states failure to manage properly religious diversity and civic pluralism. In the context of mounting competition among elites, religion has become tremendously politicised and has served more as a tactical tool used by political contenders in their own interests. Herein lies the importance of the proper management of religious diversity as a mechanism to guarantee individual freedoms and maintain the rights of religious minorities.